2021
DOI: 10.1016/j.jbc.2021.100742
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the PDB

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…The virtual docking of key proteins and active components was performed using Discovery Studio 2020 software (College of Pharmacy, Henan University of Chinese Medicine) to study their interaction. For the top 20 targets with a higher degree value in the compound-target-pathway network, the corresponding 3D structure was downloaded in the RSCB PDB database (https://www.rcsb.org/) (Richardson et al, 2021), and 22 component structures were obtained from the PubChem database, and the components were prepared using the "Prepare Ligands" module to obtain the 3D structure. For protein preparation, crystallographic water molecules were removed and then used in the "Prepare Protein" module.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The virtual docking of key proteins and active components was performed using Discovery Studio 2020 software (College of Pharmacy, Henan University of Chinese Medicine) to study their interaction. For the top 20 targets with a higher degree value in the compound-target-pathway network, the corresponding 3D structure was downloaded in the RSCB PDB database (https://www.rcsb.org/) (Richardson et al, 2021), and 22 component structures were obtained from the PubChem database, and the components were prepared using the "Prepare Ligands" module to obtain the 3D structure. For protein preparation, crystallographic water molecules were removed and then used in the "Prepare Protein" module.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Then, after lastly getting a peek at the atomic world, scientists eagerly make graphical diagrams to show us what they saw: G. Lewis and his dot structures ( 33 ), J. Richardson’s ribbon diagrams ( 34 ), and C. Levinthal’s computer graphics ( 35 ). Taking one final step to make this imagery accessible to all people is now easier than ever.…”
Section: Resultsmentioning
confidence: 99%
“…Both VC1371 and VcRfaH are able to profoundly activate mshH transcription in E. coli ; however, neither of these two proteins were predicted to contain a classical helix-turn-helix DNA-binding domain [36]. We tested the interaction between VC1371 or VcRfaH and the promoter region of mshH , and found that both of these proteins could bind to the nucleotide fragments non-specifically in vitro (Fig.…”
Section: Discussionmentioning
confidence: 99%